Apocalyptic fiction - Tate, Andrew 1971 (21st century genre fiction, 2017)
Visions of post-apocalyptic worlds have proved to be irresistible for many 21st-century writers, from literary novelists to fantasy and young adult writers. Exploring a wide range of texts, from the works of Margaret Atwood, Cormac McCarthy and David Mitchell to young adult novels such as Suzanne Collins's The Hunger Games series, this is the first critical introduction to contemporary apocalyptic fiction. Exploring the cultural and political contexts of these writings and their echoes in popular media, Apocalyptic Fiction also examines how contemporary apocalyptic texts looks back to earlier writings by the likes of Mary Shelley, H.G. Wells and J.G. Ballard. Apocalyptic Fiction includes an annotated guide to secondary readings, making this an essential guide for students of contemporary fiction at all levels.